Molecular identification of Colletotrichum gloeosporioides causing yam anthracnose in Nigeria - Abang, Mathew M.; Winter, S.; Green, K.; Hoffmann, P.; Mignouna, H.; Wolf, G. (Wiley, 2002)
Four forms of Colletotrichum representing three distinct virulence phenotypes were found associated with foliar anthracnose of yam in Nigeria: the highly virulent (= severity of disease) slow-growing grey (SGG); the moderately virulent fast-growing salmon (FGS); the weakly virulent fast-growing grey (FGG); and the moderately virulent fast-growing olive (FGO) morphotype. Isolates of the four forms were identified as C. gloeosporioides, based on morphology. The reaction of monoconidial cultures on casein hydrolysis medium (CHM), PCR-RFLP and sequence analysis of the internal transcribed spacer region of the ribosomal DNA (ITS1-5·8S-ITS2) were used to establish the identity of the yam anthracnose pathogen(s). All yam isolates were distinguished from C. acutatum by the absence of protease activity on CHM. On ITS PCR and enzymatic digestion of PCR products, all FGS, FGO and SGG isolates produced RFLP patterns identical to those of C. gloeosporioides reference isolates, while FGG isolates revealed unique ITS RFLP banding patterns. Sequence analysis of the ITS1 region and of the entire ITS region revealed that SGG, FGS and FGO isolates were highly similar (98–99% nucleotide identity) and showed 97–100% identity to C. gloeosporioides. Less than 93% similarity of these fungal isolates to reference C. acutatum and C. lindemuthianum isolates was observed. The molecular study confirmed that foliar anthracnose of yam is caused by C. gloeosporioides. While a high similarity was found among most C. gloeosporioides fungi from yam, isolates of the FGG form did not cluster with any previously described Colletotrichum species, and probably represent a distinct species.